2023
DOI: 10.3389/fpls.2023.1186162
|View full text |Cite
|
Sign up to set email alerts
|

Core microbiota of wheat rhizosphere under Upper Indo-Gangetic plains and their response to soil physicochemical properties

Abstract: Wheat is widely cultivated in the Indo-Gangetic plains of India and forms the major staple food in the region. Understanding microbial community structure in wheat rhizosphere along the Indo-Gangetic plain and their association with soil properties can be an important base for developing strategies for microbial formulations. In the present study, an attempt was made to identify the core microbiota of wheat rhizosphere through a culture-independent approach. Rhizospheric soil samples were collected from 20 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…It is well established that PGM having high enzymatic activity, phytohormone, and osmolytic metabolite-producing potential are effectively involved in plant health promotion and nutrient mobilization ( Haas and Keel, 2003 ; Shilev et al, 2019 ). A recent study conducted by Kumar et al (2023) on wheat rhizosphere in Upper-Gangetic plain, showed that various soil factors and conditions (e.g. available nitrogen, potassium, organic carbon) can be effectively improved through appropriate microbiome manipulation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that PGM having high enzymatic activity, phytohormone, and osmolytic metabolite-producing potential are effectively involved in plant health promotion and nutrient mobilization ( Haas and Keel, 2003 ; Shilev et al, 2019 ). A recent study conducted by Kumar et al (2023) on wheat rhizosphere in Upper-Gangetic plain, showed that various soil factors and conditions (e.g. available nitrogen, potassium, organic carbon) can be effectively improved through appropriate microbiome manipulation strategies.…”
Section: Introductionmentioning
confidence: 99%